Galectin-3 (MAC-2) Controls Microglia Phenotype Whether Amoeboid and Phagocytic or Branched and Non-phagocytic by Regulating the Cytoskeleton - Reichert, Fanny; Rotshenker, Shlomo (Frontiers in Cellular Neuroscience, 2019)
Myelin surrounding CNS axons breaks-down in multiple sclerosis (MS) and in Wallerian degeneration that traumatic axonal injury induces distal to lesion sites. Myelin-debris so produced is harmful to repair since it impedes remyelination in MS and regeneration of traumatized axons. These devastating outcomes are largely due to inefficient removal-by-phagocytosis of myelin-debris by microglia. Therefore, revealing mechanisms that control phagocytosis is vital. We showed before that filopodia and lamellipodia extend/engulf and then retract/internalize myelin-debris in phagocytosis. Moreover, we also showed that cofilin activates phagocytosis by advancing the remodeling of actin filaments (i.e. disassembling existing followed by assembling new filaments), causing filopodia/lamellipodia to protrude, and furthermore, that Galectin-3 (formally named MAC-2) activates phagocytosis by enhancing K-Ras.GTP/PI3K signaling that leads to actin/myosin based contraction, causing filopodia/lamellipodia to retract. To understand furthermore how Galectin-3 controls phagocytosis we presently knocked-down Galectin-3 expression in cultured primary microglia using Galectin-3 small-hairpin RNA (Gal-3-shRNA). Knocking-down Galectin-3 protein levels reduced phagocytosis extensively. Further, inhibiting nucleolin and nucleophosmin, which advance K-Ras signaling as does Galectin-3, reduced phagocytosis too. Strikingly and unexpectedly, knocking-down Galectin-3 resulted in a dramatic transformation of microglia morphology from “amoeboid-like” to “branched-like”, rearrangement of actin filaments, and inactivation of cofilin. Thus, Galectin-3 may control microglia morphology and phagocytosis by regulating the activation state of cofilin, which, in turn, affects how actin filaments organize and how stable they are. Furthermore, our current and previous findings suggest altogether that Galectin-3 activates phagocytosis by targeting the cytoskeleton twice. First, by advancing cofilin activation, causing filopodia/lamellipodia to extend/engulf myelin-debris. Second, by advancing actin/myosin based contraction through K-Ras.GTP/PI3K signaling, causing filopodia/lamellipodia to retract/internalize myelin-debris.